The Analysis of General Communication in English Language Teaching - Dasopang, Gading (Pascasarjana Universitas HKBP Nommensen, 2025)
This research examines the dynamics of communication within English Language Teaching (ELT), concentrating on the communication techniques utilized by educators, the obstacles encountered by both teachers and students, and how these elements affect student engagement and language learning. By employing a mix of semi-structured interviews and focus group discussions, the study reveals that effective communication techniques, such as interactive activities, technology use, and non-verbal cues, greatly improve learner involvement and create a nurturing learning atmosphere. However, challenges like cultural differences, diverse language proficiency levels, and anxiety associated with language use were recognized as factors that can disrupt effective communication. The findings show a strong relationship between better student outcomes and the use of effective communication techniques, indicating that language proficiency develops more robustly When learners feel supported and involved. This study adds to the body of knowledge on communication in ELT by offering helpful suggestions for teachers looking to improve their methods. It highlights the necessity of a more inclusive strategy that takes into account the various needs of children and creates a supportive learning environment in the classroom. The investigation of communication dynamics in remote and hybrid learning contexts, which have grown in importance in modern education, is one of the recommended future study avenues.